The determinants of location specific choice: Small and medium-sized enterprises in developing countries - Adeleke Oladapo Banwo; Jianguo Du; Uchechi Onokala (Journal of Global Entrepreneurship Research, 2017)
This study adopts a resource-based view to model how location specific-factors among small and medium-sized enterprises (SMEs) in coastal environments in developing economies enable them to sustain clusters and contribute to economic growth. Locations of small and medium enterprises (SMEs) play a crucial role in determining their survival. SMEs agglomerations are often due to natural resource endowments and types of business climate in their environment. The amoebic nature and economic roles they play have made them the bedrock of the micro economy in most economies. This study contributes to the literature on cross-country comparison of small and medium enterprises (SMEs) in Zhenjiang (China) and in Lagos State (Nigeria). The methodology used was mainly literature review and secondary research data from World Bank and data sets from China and Nigeria. The findings highlight an upsurge in research on SMEs in developing countries and how these enterprises have used location-specific endowments to mitigate their resource limitation predicament. The learning points are envisaged to contribute to strategic growth in international business and foreign investments, knowledge for policy makers and to generate further comparative location studies in developing countries.
Keywords: 650; Comparative; Clusters; China; Location-specific; Nigeria; Small and medium enterprises (SMEs); Zhenjiang